Guilty of Unnatural Death but HIV Positive in Transkei Region of South Africa - B Meel (Indian Journal of Forensic Medicine & Toxicology, 2022)
Background: HIV infections and crime have a complex relationship. It is difficult to understand its unnatural causation. HIV positivity has never accounted as an underlying cause of death in persons who have died unnaturally. Objective: To correlate HIV infection with non-natural deaths in the Transkei region of South Africa.Method: This is a record of a review study at Mthatha (Umtata) General Hospital. The data was collected from the office of medical superintendent and from the forensic pathology laboratory. Results: There has been an increase in the Mthatha General Hospital mortality rate by almost two- fold in last five years. Suicidal deaths like hanging have increased by one and half times. Fatal poisoning, possibly suicidal, has increased about five to sixtimes. Gunshot injuries, which may or may not be suicidal, have increased by one and half times. The accurate estimate of the prevalence of the HIV/AIDS is a necessity to measure the costs of disease for effective strategic planning. Conclusion: The HIV infection is increasing along with natural and non-natural deaths in the Transkei region of South Africa. It must be considered in the category of diminished responsibility as a mentally sick.